Legal Protection in the Oil Palm Plasma Plantation Partnership Agreement Between Limited Liability Company and Plasma Cooperative - Magdalena, Theresia; Yoyo Arifardhani; Edi Tarsono (Jurnal Ilmu Hukum Kyadiren, 2026)
The palm oil plasma core partnership agreement between plantation companies and plasma farmer cooperatives basically aims to realize a fair and balanced cooperative relationship. But in practice, agreements are often drafted unilaterally by companies and cooperative involvement tends to be formal. In addition, the non-transparent and unaccountable management of cooperatives causes the management to fail to represent the interests of plasma farmers, especially in financial management and distribution of plantation products. This condition puts plasma farmers in a weak position and vulnerable to losses. This research uses normative juridical methods with laws and regulations, conceptual, and case study approaches. The results of the study show that the weak implementation of the principles of cooperative agreements and governance has the potential to cause legal, economic, and social losses for plasma farmers. Therefore, it is necessary to strengthen the application of the principles of the agreement, improve the professionalism of cooperative management, and optimize the role of notaries to ensure balance and legal protection in plasma core partnership agreements